A Practical Guide to Writing Performance Appraisals and Letters of Recommendation - Dancer, W. Terry (American Journal of Management, 2023)
Writing performance appraisals and letters of recommendation is a difficult and timely task for some. This paper provides direction to writers about choosing applicable words for those being evaluated. This is accomplished by providing a list of words useful in describing characteristics of those under consideration. This paper considers Mentality, Presence, Disposition, Character, Knowledge, Application, and Results regarding the person under evaluation. For each characteristic noted, a list of words is provided to reflect the appropriate word/words to describe the individual. The paper also provides a template useful for getting started in the writing of performance appraisals and Letters of Recommendation.